Teachers’ Experiences on the Implementation of COVID-19 Protocols Amidst the Pandemic in Mmashadi Circuit of the Sekhukhune District - Lengwadi, Thapelo Ephraim; Molise, Habasisa Vincent; Segooa, Mapule Yvonne (Research in Social Sciences and Technology, 2024)
The global impact of the COVID-19 pandemic extended to the education sector in South Africa, prompting the implementation of preventative measures by the National Coronavirus Command Council. These COVID-19 protocols included the wearing of face masks or face shields, ensuring maximum ventilation, washing of hands, and school attendance routines to deal with overcrowded classrooms, among others. This study aimed to delve into the implementation of COVID-19 protocols in schools, focusing on the strategies utilised and the challenges teachers encountered. Employing a qualitative research methodology within a case study framework, the study involved eight teachers (five male and three female) from four schools in the Sekhukhune District, selected through purposive sampling. Data were elicited through semi-structured interviews to gain a thorough understanding of the phenomenon and coded for anonymity purposes. Aligned with the goal of the study, thematic data analysis was adopted for analysing the data. The findings revealed that teachers faced significant challenges in balancing their responsibilities in implementing COVID-19 protocols alongside making up for lost teaching time. However, alternative strategies were employed by teachers to mitigate this loss including the deployment of assistant teachers to support protocol and assist students with homework, additional security personnel to help guard and control unnecessary school visits, and for teachers to provide supplementary notes and embark on online learning. Recommendations include the increased deployment of support personnel, increased community involvement, training teachers to use online learning platforms, and for the Department of Basic Education to develop a guidance sheet to assist teachers in navigating the challenges of teaching during a pandemic.